Supporting and Enabling Scholarship: Developing and Sharing Expertise in Online Learning and Teaching - Fiona Barnes; Sue Cole; Ingrid Nix (Edinburgh Napier University in collaboration with Aston University, the Universities of Dundee and Auckland, 2018)
In a highly competitive, rapidly changing higher education market, universities need to be able to generate pedagogical expertise quickly and ensure that it is applied to practice. Since teaching approaches are constantly evolving, partly responding to emerging learning technologies, there is a need to foster ways to keep abreast on an ongoing basis. This paper explores how a small-scale project, the Teaching Online Panel (TOP), used scholarship investigations and a bottom-up approach to enhance one particular aspect of academic practice - online learning and teaching. The experiences of TOP are useful for identifying:  • how a scholarship approach can help develop academic expertise • its contribution to enhancing understanding of staff's different roles in the University • ways of developing the necessary supportive network for those undertaking such scholarship • the effectiveness of staff development which is peer-led rather than imposed from above • how practical examples can stimulate practice development • the relevance of literature on communities of practice and landscapes of practice for scholarship • the important role of 'brokers' to facilitate the dissemination of scholarship findings • the benefits to the brokers' own professional roles • the challenges of sustaining such an approach and lessons learnt. This study has relevance for those involved in supporting scholarship or delivering staff development in Higher Education.